Heat transfer of fluid with a moving heat source - Quang, Vu Duy (Vietnam Journal of Mechanics, 1994)
Investigation of free, convection in fluid heated by front combustion synthesis is presented. Characteristic parameter for problem is received. Three stages of development of free convection are distinguished.